Perfusion estimation using contrast enhanced three-dimensional subharmonic ultrasound imaging: an in vivo study - Sridharan, Anush (2013)
OBJECTIVES: The ability to estimate tissue perfusion (in mL/min/g) in vivo using contrast-enhanced three-dimensional (3D) harmonic and subharmonic ultrasound imaging was investigated. MATERIALS AND METHODS: A Logiq 9 scanner (GE Healthcare, Milwaukee, WI) equipped with a 4D10L probe was modified to perform 3D harmonic imaging (HI; f(transmit) = 5 MHz and f(receive) = 10 MHz) and subharmonic imaging (SHI; f(transmit)= 5.8 MHz and f(receive)= 2.9 MHz). In vivo imaging was performed in the lower pole of both kidneys in five open-abdomen canines after injection of the ultrasound contrast agent (UCA) Definity (Lantheus Medical Imaging, N Billerica, MA). The canines received a 5 μL/kg bolus injection of Definity for HI and a 20 μL/kg bolus for SHI in triplicate for each kidney. Ultrasound data acquisition was started just prior to injection of UCA (in order to capture the wash-in) and continued until washout. A microvascular staining technique based on stable (non-radioactive) isotope-labeled microspheres (Biophysics Assay Laboratory Inc, Worcester, MA) was used to quantify the degree of perfusion in each kidney (the reference standard). Ligating a surgically exposed branch of the renal arteries induced lower perfusion rates. This was followed by additional contrast-enhanced imaging and microsphere injections to measure post-ligation perfusion. Slice data were extracted from the 3D ultrasound volumes and used to generate time-intensity curves off-line in the regions corresponding to the tissue samples used for microvascular staining. The mid-line plane was also selected from the 3D volume (as a quasi-2D image) and compared to the 3D imaging modes. Perfusion was estimated from the initial slope of the fractional blood volume uptake (for both HI and SHI) and compared to the reference standard using linear regression analysis. RESULTS: Both 3D HI and SHI were able to provide visualization of flow and, thus, perfusion in the kidneys. However, SHI provided near complete tissue suppression and improved visualization of UCA flow. Microsphere perfusion data were available for 4 canines (1 was excluded because of an error with the reference blood sample) and showed an average perfusion of 9.30 ± 6.60 and 5.15 ± 3.42 mL/min/g pre and post ligation, respectively. The reference standard showed significant correlation with overall 3D HI perfusion estimates (r=0.38; P=0.007), but correlated more strongly with 3D SHI (r=0.62; P<0.001). Additionally, these results showed an improvement over the quasi-2D HI and SHI perfusion estimates (r=−0.05 and r=0.14) and 2D SHI perfusion estimates previously reported by our group (r=0.57) CONCLUSIONS: In this preliminary study, 3D contrast-enhanced nonlinear ultrasound was able to quantify perfusion in vivo. 3D SHI resulted in better overall agreement with the reference standard than 3D HI and was superior to previously reported 2D SHI results. 3D SHI outperforms the other methods for estimating blood perfusion, due to the improved visualization of the complete perfused vascular networks.